Navigating Policy trends and Advancing Health care through Immunization Excellence - Agarwalla, Rashmi; Bhattacharyya, Himashree; Phukan, Purabi; Zaman, Forhad Akhtar (Indian Journal of Community Health, 2024)
Immunization is a key component of primary health care. Several new vaccines have been incorporated in the immunization schedule over the last few years. However, the immunization coverage has not reached up to the mark with several challenges to be addressed like demography and infrastructure related issues, issues related to recording and reporting, vaccine and logistic management as well as management of adverse reactions. This article highlights the key deliberations of a CME cum consultative workshop on navigating policy trends and developing effective solutions to key challenges faced by the stakeholders at various levels in effective delivery of immunization services. The program focussed on new vaccines in pipe line for India and key considerations in new vaccine introduction along with some novel topics like bio repository in immunization and special immunization clinics for adults and travellers.